Polarity Sensitivity of Human Auditory Nerve Fibers Based on Pulse Shape, Cochlear Implant Stimulation Strategy and Array - Heshmat, Amirreza; Sajedi, Sogand; Schrott-Fischer, Anneliese; Rattay, Frank (Frontiers in Neuroscience, 2021)
Neural health is of great interest to determine individual degeneration patterns for improving speech perception in cochlear implant (CI) users. Therefore, in recent years, several studies tried to identify and quantify neural survival in CI users. Among all proposed techniques, polarity sensitivity is a promising way to evaluate the neural status of auditory nerve fibers (ANFs) in CI users. Nevertheless, investigating neural health based on polarity sensitivity is a very challenging and complicated task that involves various parameters, and the outcomes of many studies show contradictory results of polarity sensitivity behavior. Our computational study benefits from an accurate three-dimensional finite element model of a human cochlea with realistic human ANFs and determined ANFs degeneration pattern of peripheral part with a diminishing of axon diameter and myelination thickness based on degeneration levels. In order to see how different parameters may impact the polarity sensitivity behavior of ANFs, we investigated polarity behavior under the application of symmetric and asymmetric pulse shapes, mono- and multipolar CI stimulation strategies, and a perimodiolar and lateral CI array system. Our main findings: (1) Action potential (AP) initiation sites occurred mainly in the peripheral site in the lateral system regardless of stimulation strategies, pulse polarities, pulse shapes, cochlear turns, and ANF degeneration levels. However, in the perimodiolar system, AP initiation sites varied between peripheral and central processes depending on stimulation strategies, pulse shapes, and pulse polarities. (2) In perimodiolar array, clusters formed in threshold values based on cochlear turns and degeneration levels for multipolar strategies only when asymmetric pulses were applied. (3) In the perimodiolar array, a declining trend in polarity (anodic threshold/cathodic threshold) with multipolar strategies was observed between intact or slight degenerated cases and more severe degenerated cases. Whereas, in the lateral array, cathodic sensitivity was noticed for intact and less degenerated cases and anodic sensitivity for cases with high degrees of degeneration. Our results suggest that a combination of asymmetric pulse shapes, more focusing stimulation strategies, as well as considering the distances to the modiolus wall allows us to distinguish the degeneration patterns of ANFs across the cochlea.